SH.SEYITOVTIŃ «XALQABAD» ROMANINIŃ LEKSIKALIQ O‘ZGESHELIKLERI - Erjanova, D.Q. (SCIENCE and SOCIETY, 2023)
In the article the lexical features of the novel “Khalkabad” of the great Karakalpak poet Sh.Seitov, poet’s skills of using synonyms, antonyms, homonyms, phraseologisms is learnt.
Keywords: karakalpak language; Sh.Seitov; lexics; novel; synonym; antonym; omonym; obsolete words and phraseologisms